Evaluation of bioactivities of Phyllanthus emblica seed - Suttijit Sriwatcharakul (My University, 2020)
This research aim to study bioactivity of seed extract compare with fruit extract of Indian gooseberry; Phyllanthus emblica that use as medicinal plant widely in Thailand. Analyzed the efficacy of free radical scavenging by using DPPH radical scavenging assay reveal that the highest antioxidant activity found in the highest concentration, 10 mg/ml and both fruit and seed extracts had non-significant percentage of reduction as α-tocopherol. The determination of phytochemical exhibited that seed extract had the higher contents of tannin and flavonoid than fruit extract as 126.71 mg TAE/g extract and 1016.25 mg QE/g extract, respectively. Cytotoxicity studied of extracts against human breast adenocarcinoma cell line by MTT assay at the maximum concentration 10000 μg/ml found that seed extract had more toxicity than fruit extract at 68.98% and 35.57%. According to the bioactivities results, the seed of Phyllanthus emblica has potential to replace the fruit for medical aspects to add value of this plant.
Keywords: Phyllanthus emblica; Phytochemical; Phyllanthus; Tannin; Phytochemistry and Bioactivity Studies